Adsorption of Uranyl ions on Amine-functionalization of MIL-101(Cr) Nanoparticles by a Facile Coordination-based Post-synthetic strategy and X-ray Absorption Spectroscopy Studies - Zhang, Jian-Yong (Sci Rep, 2015)
By a facile coordination-based post-synthetic strategy, the high surface area MIL-101(Cr) nanoparticles was functionallized by grafting amine group of ethylenediamine (ED) on coordinatively unsaturated Cr(III) centers, yielding a series of ED-MIL-101(Cr)-based adsorbents and their application for adsorption of U(VI) from aqueous solution were also studied. The obtained ED-functionallized samples with different ED contents were characterized by powder X-ray diffraction (PXRD), scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), FTIR, elemental analysis (EA) and N(2) adsorption and desorption isothermal. Compared with the pristine MIL-101(Cr) sorbents, the ED-functionallized MIL-101(Cr) exhibits significantly higher adsorption capacity for U(VI) ions from water with maximum adsorption capacities as high as 200 mg/g (corresponding to 100% extraction rate) at pH of 4.5 with ED/Cr ratio of 0.68 and the sorbed U(VI) ions can easily be desorbed at lower pH (pH ≤ 2.0). The adsorption mode of U(VI) ions and effects of grafted ED on the MIL-101(Cr) frameworks were also been studied by X-ray absorption spectroscopy (XAS). We believe that this work establishes a simple and energy efficient route to a novel type of functional materials for U(VI) ions extraction from solution via the post-synthetic modification (PSM) strategy.